Some anthropological and clinical aspects of nasal morphology - Jarvis, John Fulford (Department of Human Biology, 2020)
In the human species as in all the animal kingdom considerable individual variation is encountered, differences being seen in morphology, size, activity, and in reaction manifests itself in differing susceptibility to disease and to the effects of injury; an epidemic causing an individual to succumb while another escapes, one dies from a trivial electric shock while another survives contact with a high voltage. The factors known to be involved in this variability of response includes race, heredity, nutritional state, climate, social environment, psychological outlook and bodily morphology. The gross anatomy of certain organs of the body such, for example, as the endocrine glands has a little or no relation to their fundamental efficiency, so that the thyroid gland would probably produce its secretion equally well were it of a different shape or situated in another part of the body.